Filterless pseudo-power-based sensorless commutation method for BLDC motors. (2018) - Rad, Shahin Mahdiyoun; Azizian, Mohammad Reza
This paper presents a new commutation technique for position-sensorless control of BLDC motors called as pseudo-power-based commutation method. The proposed method does not require any low-pass filter, because it utilises the unfiltered line-to-line voltages. Moreover, no phase shifter is needed. Unfiltered voltages have notches resulted from current commutation that deteriorate the commutation signals extracted from the motor line voltages. Therefore, it is proposed to use the pseudo-power signs of the three phases of the motor as the auxiliary signals to compensate the commutation ripples effects. This method does not involve speed-dependent phase-delay. The simulation has been run in MATLAB/Simulink and the real-time implementation has been done using Advantech PCI-1716 multifunction card to justify the effectiveness of the proposed method.